Designing a ship course controller by applying the adaptive backstepping method - Witkowska, Anna; Śmierzchalski, Roman (Zielona Góra: Uniwersytet Zielonogórski)
The article discusses the problem of designing a proper and efficient adaptive course-keeping control system for a seagoing ship based on the adaptive backstepping method. The proposed controller in the design stage takes into account the dynamic properties of the steering gear and the full nonlinear static maneuvering characteristic.
Keywords: autopilot; adaptive control; nonlinear control; backstepping; genetic algorithms